2010
DOI: 10.1116/1.3420430
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of structure and hardness of rf magnetron sputtered silicon carbonitride films

Abstract: Articles you may be interested inStructure and properties of ZrN coatings deposited by high power impulse magnetron sputtering technology Structure and mechanical properties of nanoscale multilayered CrN/ZrSiN coatings J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Depending on the conditions (substrate temperature, deposition environment pressure etc. ), composition and used methods, carbides can possess hardnesses from 9 to 35 GPa [37][38][39][40][41][42][43]. The higher hardness values are usually obtained at higher temperatures than 300 � C and enable development of harder films (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Elastic Moduli and Hardnessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the conditions (substrate temperature, deposition environment pressure etc. ), composition and used methods, carbides can possess hardnesses from 9 to 35 GPa [37][38][39][40][41][42][43]. The higher hardness values are usually obtained at higher temperatures than 300 � C and enable development of harder films (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Elastic Moduli and Hardnessesmentioning
confidence: 99%
“…The higher hardness values are usually obtained at higher temperatures than 300 � C and enable development of harder films (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In this regard, the deposited ALD thin films showed comparable or even higher values [37][38][39].…”
Section: Elastic Moduli and Hardnessesmentioning
confidence: 99%
“…Research has been done on the effect of pressure and nitrogen on the hardness of the Si-C-N coatings [10][11][12][13][14][15][16][17]. The research on different aspect of single-layer hard SiCN coatings has also been reported by one of the authors Mishra et al in the literature, where it showed very fine nanocrystalline dispersion of size 2-10 nm in SiCN amorphous matrix [18,19]. The films were very hard ranging between 10 and 35 GPa dependent on the deposition parameters.…”
Section: Introductionmentioning
confidence: 90%
“…6a-b. The peaks of the spectra are shown in Table 4 with the respective chemical groups referring to [18,24,32,33]. The analysis reveals that the dominant peaks include SiO x in-phase stretching and the Si-O Table 7 Binding energies of chemical bonds corresponding with the XPS spectra of Si 2p , O 1s , and C 1s .…”
Section: Chemical Compositions and Chemical Bondsmentioning
confidence: 99%